2010
DOI: 10.1093/geront/gnq063
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions, Knowledge, Incentives, and Barriers of Brain Donation Among African American Elders Enrolled in an Alzheimer's Research Program

Abstract: Culturally relevant educational protocols need to be created for use with African American older adults. These protocols should include information about brain donation procedures, rates of AD among Black elders, and potential benefits of donation to Black communities; inclusion of religious figures, family, and peers in donation education and decisions; and methods to address mistrust, including cultural competence trainings for staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 26 publications
3
74
0
Order By: Relevance
“…Bonner et al found family disagreement about donation, concern over funeral arrangements, and inadequate information about the donation process as barriers [10]. Our work also suggests that misconceptions about brain donation procedures exist, and racial mistrust may deter individuals from consenting to brain donation [12]. Health literacy, or the degree to which one is able to gather, process, and understand relevant medical information to make an appropriate health-related decision, may also play a role in donation assent.…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…Bonner et al found family disagreement about donation, concern over funeral arrangements, and inadequate information about the donation process as barriers [10]. Our work also suggests that misconceptions about brain donation procedures exist, and racial mistrust may deter individuals from consenting to brain donation [12]. Health literacy, or the degree to which one is able to gather, process, and understand relevant medical information to make an appropriate health-related decision, may also play a role in donation assent.…”
Section: Introductionmentioning
confidence: 60%
“…In our prior work on barriers and incentives to brain donation among African American older adults [12], participants reported that group-based discussions about brain donation that include family members are critical to increasing donation knowledge and facilitating donor decisions. In 2009, we held two focus groups with a subset of African American registry participants ( n = 11 with one loved one attending) to develop and refine the discussion content for the informational intervention in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Others believe that past abuses, such as the Tuskegee syphilis study, have soured the relationship between researchers and racial and ethnic minorities (Wendler et al, 2006). This belief is reinforced by evidence from focus groups with African Americans with AD and their caregivers (Connell, Shaw, Holmes, & Foster, 2001;Lambe, Cantwell, Islam, Horvath, & Jefferson, 2011).…”
Section: Participation In Research Studiesmentioning
confidence: 99%